Case Study IBT® Learning Content Management. The Conception and Production of E-Learning Content Based on MS Word Templates. - Lipps, Anja; Neuhoff, Christina (International Journal of Advanced Corporate Learning (iJAC), 2017)
This document gives you an overview of the features of the rapid e-learning production tool IBT® Learning Content Management which has been awarded with the IELA 2017 in the section Business Division. To illustrate purpose and possibilities, we describe two examples as show cases.